Acute airway eosinophilic inflammation model in mice induced by ovalbumin, house dust mite, or shrimp tropomyosin: a comparative study - Xu, Liangyu; Wei, Zichen; Wu, Rongfang; Kong, Siqi; Bin, Jinlian; Gao, Yuxin; Fang, Lei (Frontiers in Allergy, 2025)
BackgroundOvalbumin (OVA) and house dust mite (HDM) are widely used allergenic proteins in murine models of allergic asthma. In our previous studies, shrimp tropomyosin (ST) was shown to induce type I hypersensitivity, including asthma-like responses. Here, we compared airway eosinophilic inflammation models induced by OVA, HDM, or ST using a protocol of three intraperitoneal (i.p.) sensitizations followed by a single intratracheal (i.t.) allergen challenge.MethodsC57BL/6J mice were sensitized via three i.p. injections of OVA, HDM, or ST mixed with Al(OH)3, followed by a single i.t. challenge with the respective allergen. Lung transcriptomic analysis, plasma IgE levels, bronchoalveolar lavage (BAL) fluid cell counts, cytokine and chemokine mRNA levels, and histopathological assessments were performed to evaluate airway inflammation.ResultsA single i.t. challenge with ST or HDM significantly increased the lung-to-body weight ratio, eosinophil infiltration, and mucus hypersecretion, accompanied by elevated mRNA levels of Th2 cytokines (Il-4, Il-5, Il-13) and increased the total cell count and eosinophil count in the BAL fluid. In contrast, OVA induced only mild eosinophilic inflammation, suggesting that repeated exposures may be required to elicit a robust allergic response. RNA sequencing and qRT-PCR further identified key chemokines associated with eosinophil recruitment (Ccl-11, Ccl-24), Th2 polarization (Ccl-17), and neutrophil activation (Cxcl-1).ConclusionA single i.t. challenge of ST, similar to HDM, exhibits a potent ability to induce eosinophilic inflammation and Th2-type immune responses in a murine model of allergic asthma, surpassing the effects of OVA.